1998
DOI: 10.1105/tpc.10.4.623
|View full text |Cite
|
Sign up to set email alerts
|

Accumulation of an Acidic Dehydrin in the Vicinity of the Plasma Membrane during Cold Acclimation of Wheat

Abstract: Expression of the acidic dehydrin gene wcor410 was found to be associated with the development of freezing tolerance in several Gramineae species. This gene is part of a family of three homologous members, wcor410 , wcor410b , and wcor410c , that have been mapped to the long arms of the homologous group 6 chromosomes of hexaploid wheat. To gain insight into the function of this gene family, antibodies were raised against the WCOR410 protein and affinity purified to eliminate cross-reactivity with the WCS120 de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
0
5

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 376 publications
(195 citation statements)
references
References 23 publications
6
184
0
5
Order By: Relevance
“…These proteins, characterised by the presence of highly conserved segments in amino acid sequence named Y-, Sand K-segments (Close 1996;Close 1997) or A-and Esegments specifically in Pinaceae (Perdiguero et al 2012a), have been proposed to play a key role in the response to drought stress in plants. This is because they are involved in preserving and maintaining cell functions during dehydration (Eriksson and Harryson 2011;Kosová et al 2010;Rorat 2006), probably via stabilisation of membranes by hydrophobic interactions (Campbell and Close 1997;Danyluk et al 1998;Koag et al 2003), chaperone activity (Kovacs et al 2008a;Kovacs et al 2008b) or antioxidant activity preventing excessive reactive oxygen species (ROS) formation (Hara et al 2005;Sun and Lin 2010). The overexpression of dehydrins in Arabidopsis or tobacco enhanced tolerance to drought and other stresses (Brini et al 2007;Hara et al 2003;Puhakainen et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…These proteins, characterised by the presence of highly conserved segments in amino acid sequence named Y-, Sand K-segments (Close 1996;Close 1997) or A-and Esegments specifically in Pinaceae (Perdiguero et al 2012a), have been proposed to play a key role in the response to drought stress in plants. This is because they are involved in preserving and maintaining cell functions during dehydration (Eriksson and Harryson 2011;Kosová et al 2010;Rorat 2006), probably via stabilisation of membranes by hydrophobic interactions (Campbell and Close 1997;Danyluk et al 1998;Koag et al 2003), chaperone activity (Kovacs et al 2008a;Kovacs et al 2008b) or antioxidant activity preventing excessive reactive oxygen species (ROS) formation (Hara et al 2005;Sun and Lin 2010). The overexpression of dehydrins in Arabidopsis or tobacco enhanced tolerance to drought and other stresses (Brini et al 2007;Hara et al 2003;Puhakainen et al 2004).…”
Section: Introductionmentioning
confidence: 98%
“…Highly-conserved polar regions of dehydrins have been suggested to hydrogen-bond with polar regions of macromolecules, acting essentially as a surfactant, to prevent coagulation under conditions of cellular dehydration or low temperatures [18]. Immunolocalization and subcellular fractionation results have showed that members of the dehydrin family are present in the nucleus, cytoplasm, and plasma membrane [19,20]. Recently we have found that two dehydrin-like proteins (dlps) accumulated in mitochondria of Triticum aestivum (L.) (winter wheat), Secale cereale (L.) (winter rye), and in Zea mays (L.) (corn) in response to cold [21].…”
Section: Introductionmentioning
confidence: 99%
“…Most of them accumulate in all tissues upon water deficit although there are those that preferentially respond to particular stress conditions. Some dehydrins are strongly accumulated in response to low-temperature treatments but not to drought or salinity [99]; other group 2 members are not induced in response to low temperatures, while a small number of dehydrins show an unusual constitutive expression [100]- [102]. However, it is not possible to assign a specific accumulation pattern to particular group or subgroup.…”
Section: Sub Cellular Localization and Expression Profilesmentioning
confidence: 86%
“…LEA proteins being highly hydrophilic are not expected to interact with cellular membranes in hydrated condi-tions, but interaction cannot be excluded through α-helices in a dehydrating cell. Among group 2 LEA proteins, wheat WCOR414 and Arabidopsis LTi29 acidic dehydrins were immunodetected in the vicinity of the plasma membrane during cold acclimation [100] [138] and maize dehydrins were observed in association to membranes of protein and lipid bodies [139]. Maize native and recombinant dehydrin DHN (Rab17) binds in vitro to anionic lipid vesicles and binding produces an increase in amphipathic α-helix (a structural element that interacts to membranes and proteins); both binding and gain in conformation were attributed to the K-segment [140] [141].…”
Section: Membrane Protectionmentioning
confidence: 99%